Evaluation of Fungicides and Genotypes Against Anthracnose Disease of Mungbean Caused by Colletotrichum lindemuthianum - Singh, Shwetank; Prasad, Durga; Singh, Virendra Pratap (International Journal of Bio-resource and Stress Management, 2022)
Mungbean [Vigna radiata (L.) Wilczek]is an important crop grown extensively in Bundelkhand region of Uttar Pradesh. Despite the multifaceted importance of this crop, its production could not be stabilized in the Uttar Pradesh as well as in the country. There are several biotic and abiotic constraints hampering the production of mungbean crop. Among the diseases, anthracnose disease caused by Colletotrichum lindemuthianum isone of the most important fungal diseases of mungbean in India. In recent past, it has become a major threat for mungbean cultivation particularly in Bundelkhand region of Uttar Pradesh during the Kharif crop season. Field experiments were conducted during July to September in 2019 and 2020 to find out a suitable management option for anthracnose in mungbean. Nine different fungicides and 190 mungbean germplasm were assessed against anthracnose. Twice sprays of Carbendazim at 1st appearance of symptoms at15 days interval gave the maximum reduction in incidence and severity of anthracnose i.e. 51.12% and 64.56%, respectively along with significant enhancement (53.39%) in grain yield during both the crop seasons. The second best effective fungicide for reduction of incidence and severity was combination of Carbendazim + Mancozeb followed by Azoxystrobin and Tebuconazole. Out of 190 mungbean germplasm, evaluated for resistance against anthracnose disease during two crop seasons, four genotypes viz., Pairy Mung, PMG-991, MGG-295 and Kopargaon were found to be moderately resistant against anthracnose disease. None of the germplasm were found to be resistant.